2010
DOI: 10.1095/biolreprod.109.081984
|View full text |Cite
|
Sign up to set email alerts
|

WEE2 Is an Oocyte-Specific Meiosis Inhibitor in Rhesus Macaque Monkeys1

Abstract: WEE1 homolog 2 (WEE2, also known as WEE1B) is a newly identified member of the WEE kinase family that is conserved from yeast to humans. The aim of the present study was to determine the spatiotemporal expression pattern and the function of WEE2 during oocyte maturation in a nonhuman primate species, the rhesus macaque. Among 11 macaque tissues examined, WEE2 transcript is predominantly expressed in the ovary and only weakly detectable in the testis. Within the ovary, WEE2 mRNA is exclusively localized in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 45 publications
(61 reference statements)
2
43
0
1
Order By: Relevance
“…3Ab), indicating the presence of NLS in pWEE1B as reported for the mouse, human and rhesus monkey WEE1Bs [1,3,5]. We found a putative NLS sequence, KRK, at 173-175 in pWEE1B (Fig.…”
Section: Localization Of Pwee1b and Its Involvement In The Meiotic Arsupporting
confidence: 80%
See 3 more Smart Citations
“…3Ab), indicating the presence of NLS in pWEE1B as reported for the mouse, human and rhesus monkey WEE1Bs [1,3,5]. We found a putative NLS sequence, KRK, at 173-175 in pWEE1B (Fig.…”
Section: Localization Of Pwee1b and Its Involvement In The Meiotic Arsupporting
confidence: 80%
“…The localization of pWEE1B was examined in the present study, and exclusive nuclear localization was revealed in the fully grown meiotically arrested oocytes. The nuclear localization of WEE1B has already been reported in mice, humans and rhesus monkeys [1,3,5], and this is also the case in pigs, indicating the presence of a nuclear localization signal (NLS) in pWEE1B. In the present study, we mutated a KRK sequence, corresponding to the NLS of mWEE1B [5], to KTT and overexpressed it in oocytes maintained at the GV stage.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…To increase analytical depth, the sample complexity was reduced by a prefractionation step using strong cation exchange chromatography (SCX), which separated the iTRAQ-labeled peptides on the basis of their charge. Peptides were eluted from the SCX column (Biobasic, Thermo Scientific, Rockford, IL, USA) stepwise using eight different potassium chloride (KCl) concentrations (0, 45,75,90,110,135,175, and 350 mM KCl) and subsequently desalted using C18 spin columns (Pierce, Thermo Scientific, Rockford, IL, USA). SCX fractions were evaporated to dryness under vacuum (vacuum concentrator, Bachofer) and stored at −80°C until LC−MS/MS analysis.…”
Section: Itraq Labeling and Scx Prefractionationmentioning
confidence: 99%